A case of infective endocarditis caused by beta-lactam resistant Streptococcus alactolyticus - Melina Ntoga; Vasileios Emmanouil; Eirini Terzi; Vasilios Petrakis; Periklis Panagopoulos; Dimitrios Papazoglou (European Journal of Case Reports in Internal Medicine)
Background: Streptococcus alactolyticus is a rare cause of human infections, with limited reports of infective endocarditis (IE). Case report: We present a case of a 68-year-old male with severe aortic stenosis who developed S. alactolyticus associated IE resistant to beta-lactams. Initial treatment with vancomycin and gentamicin led to temporary improvement, but the patient later developed complications, including splenic infarction and an aortic root abscess. Despite intensified antimicrobial therapy, he ultimately succumbed to multiorgan failure. Conclusion: This case underscores the importance of early identification of resistant pathogens, appropriate antibiotic selection, and vigilant monitoring for complications. The rising incidence of beta-lactam resistance in streptococcal infections highlights the need for ongoing epidemiological surveillance and research to optimize treatment strategies.